2013
DOI: 10.1371/journal.pone.0073867
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Antimicrobial Peptides Fail to Eradicate Helicobacter pylori Infection Due to Selective Induction and Resistance

Abstract: BackgroundAlthough antimicrobial peptides protect mucus and mucosa from bacteria, Helicobacter pylori is able to colonize the gastric mucus. To clarify in which extend Helicobacter escapes the antimicrobial defense, we systematically assessed susceptibility and expression levels of different antimicrobial host factors in gastric mucosa with and without H. pylori infection.Materials and MethodsWe investigated the expression levels of HBD1 (gene name DEFB1), HBD2 (DEFB4A), HBD3 (DEFB103A), HBD4 (DEFB104A), LL37 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…Furthermore, cag PAI-dependent induction of BD2 was also observed in MKN45 cells infected with H. pylori (38). The binding of BD2 on the surface of H. pylori cells was recently shown (39), and it is a phenomenon that may explain the absence of detection of BD2 proteins in the cell culture supernatants. Our results support the view that BD2 is expressed in response to early and chronic H. pylori infection and that the cag PAI is involved in this antimicrobial peptide mRNA induction.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, cag PAI-dependent induction of BD2 was also observed in MKN45 cells infected with H. pylori (38). The binding of BD2 on the surface of H. pylori cells was recently shown (39), and it is a phenomenon that may explain the absence of detection of BD2 proteins in the cell culture supernatants. Our results support the view that BD2 is expressed in response to early and chronic H. pylori infection and that the cag PAI is involved in this antimicrobial peptide mRNA induction.…”
Section: Discussionmentioning
confidence: 91%
“…While the study of Nuding et al. revealed that HBD1 transcripts did not differ significantly between H. pylori‐ negative and ‐positive subjects, another study reported just the opposite . Not only did H. pylori ‐infected patients express less HBD1 in the gastric mucosa than the healthy counterparts, but notably, this correlates with an increased burden of infection and a higher inflammatory score.…”
Section: Host and Bacteria Interplay: Evolution Of Virulence Factorsmentioning
confidence: 92%
“…H. pylori in particular utilizes host cholesterol to change its membrane makeup gaining resistance against LL- 37 (McGee et al 2011 ), and, while inducing hBD-2, it seemingly avoids the upregulation of hBD-3 (Bauer et al 2013 ). The latter, while having the potential to kill H. pylori effectively, can consequently not help in eradicating it from gastric epithelia, while hBD-2, which is readily induced, only shows minor activity against the pathogen (Nuding et al 2013 ).…”
Section: Amp In the Upper Gastrointestinal Tractmentioning
confidence: 99%